Efficiency of postoperated microwave therapy of the patients with inflammated tubo-ovarian tumors - I. D. Evtushenko; A. P. Romanova (Бюллетень сибирской медицины)
The aim of the research is the study of efficiency of early postoperative rehabilitation of patients with purulent inflammatory formations of uterine appendages with microwave therapy. Postoperative treatment of 36 women-patients with the use of combined skin and intravaginal microwave exposure was done. The clinical characteristics of postoperative period and the results of the therapy in 18 month were studied. Dynamical changes of quantitative characteristics of cells at leukemia, of C-reactive protein, content in blood serum, in cervical canal and endometrium of tumor necrosis factor-alpha, interleukin-1 beta and interleukin-6 were estimated. If comparing with the patients who didn’t get physiotherapy exposure the use of microwave therapy at the patients with purulent tubo-ovarian formations was followed by earlier disappearance of inflammation, restoration of quantitative characteristics of leucocytes in blood, normalization of C-reactive protein concentration in blood serum and normal characteristics of erythrocyte sedimentation rate. Diminution of tumor necrosis factor-alpha in blood serum, interleukin-1 beta and interleukin-6, reduction of concentration in cervical canal and endometrium interleukin-6 were observed. In the postoperative period under the microwave therapy womenpatients had pain in pelvis, disturbance of menstrual cycle, 26,5% of women had the reproductive function to be restored.